The Effect of the Talking Stick Learning Model on Student Learning Outcomes in Science Subject - Kaharu, Saritan N.; Rahman, Abdul; Pahriadi, Pahriadi; Aban, Trisilawati A. (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to determine whether there is an influence of the Talking stick learning model on student learning outcomes in the science subject of class V SD Negeri Tondo. This research method uses a quasi-experimental research method, research design using a non-equivalent control group design. For research techniques using purposive sampling technique. The sample in this study amounted to 54 students, consisting of 27 VA class students as the experimental class and 27 students of VB class as control class. The research instrument is a multiple choice test with 18 questions. The data is statistically analyzed to find out significant achievements between the two groups, the experimental group used the talking stick learning model with the help of learning media obtained an average posttest score of 81.12 while the control class using the conventional model obtained an average posttest score of 49.95. Based on the significant value of the Paired Sample T Test is 0.000, because the significant value of the T-test <0.05 (0.000 <0.05) carried out at a significant level of 5% (0.05), then Ha is accepted and Ho is rejected. So it can be concluded that there is the influence of the Talking Stick learning model on science learning outcomes of V grade students at SD Negeri Tondo.